Ocorrencia de "filodia" em mandioca - Fukuda, C.; Paguio, O. de la R.; Lozano, J.C. (1984)
Phyllody, previously unreported in Brazil, was observed in several cassava cv. and hybrids planted in exptl. plots of the Centro Nacional de Pesquisa de Mandioca e Fruticultura in Cruz das Almas. The effect of the disease on production is not known; however, it poses a serious threat to the cassava breeding program. Studies to identify the causal agent, methods of transmission, and control of the disease are in progress. (AS)